Mediterranean Diet and its Effects on Silent Brain Infarcts in a Cohort of Patients With Atrial Fibrillation. (November 2022) - Escudero-Martínez, Irene; Mancha, Fernando; Vega, Ángela; Zapata, Montserrat; Ocete, Rafael F; Álvarez, Lucía; Algaba, Pilar; López-Rueda, Antonio; Piñero, Pilar; Fajardo, Elena; Fernández-Engo, José Román; Martín-Sánchez, Eva M; et al.
Background and Aims: The benefits of Mediterranean Diet (MeDiet) in prevention of cardiovascular diseases (CVD) in general and ischemic stroke (IS) have been extensively studied and reported. We hypothesize that the consumption of nutrients typical of MeDiet would also reduce the rate of silent brain infarcts (SBI) among AF patients. Methods and Results: Patients with a history of AF who scored 0 to 1 in the CHADS2 score, ⩾50 years and with absence of neurological symptoms were selected from Seville urban area using the Andalusian electronic healthcare database. A 3T brain MRI was performed to all participants. Demographic and clinical data and food-frequency questionnaire (FFQ) were collected. Of the 443 scanned patients, 66 presented SBI. Of them 52 accepted to be scheduled for a clinical visit and were included in the diet sub study and 41 controls were matched per age and sex. There were no statistically significant differences in baseline characteristics. After logistic regression analysis, we found that a higher consumption of fiber from fruit was independently associated with a lower risk of SBI, while a higher consumption of high glycemic load (GL) foods was associated with a higher risk of SBI in a population with AF Conclusion: Our findings support that MeDiet could be suggested as a prevention strategy for SBI in patients with AF.